1998
DOI: 10.1074/jbc.273.33.21246
|View full text |Cite
|
Sign up to set email alerts
|

A Carboxyl-terminal Cys2/His2-type Zinc-finger Motif in DNA Primase Influences DNA Content inSynechococcus PCC 7942

Abstract: The DNA primase gene, dnaG, has been isolated from the cyanobacterium Synechococcus PCC 7942. It is not part of a macromolecular synthesis operon but is cotranscribed with pheT and located adjacent to the metallothionein divergon, smt. caused an increase in intensity, and a reduction in wavelength, of Trp fluorescence at the tip of the predicted zinc-finger, while EDTA caused the converse. Cells containing a single chromosomal codon substitution (C597S), altering the zinc-finger, were generated by exploiting Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…There is evidence to support a role for mammalian MT in the donation of Zn 2ϩ to Zn 2ϩ -binding proteins (25)(26)(27)(28)(29)(30). It has been hypothesized that SmtA may donate Zn 2ϩ to DNA primase (DnaG), which in Synechococcus PCC 7942 contains two Zn 2ϩ binding sites and is encoded by a gene that is located next to the smtA gene (31). Similarities between metal binding domains provided a clue to the existence of interaction between a copper chaperone and its receptor (32).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to support a role for mammalian MT in the donation of Zn 2ϩ to Zn 2ϩ -binding proteins (25)(26)(27)(28)(29)(30). It has been hypothesized that SmtA may donate Zn 2ϩ to DNA primase (DnaG), which in Synechococcus PCC 7942 contains two Zn 2ϩ binding sites and is encoded by a gene that is located next to the smtA gene (31). Similarities between metal binding domains provided a clue to the existence of interaction between a copper chaperone and its receptor (32).…”
Section: Discussionmentioning
confidence: 99%
“…8, which is published as supplemental data; A.K.R., M.D.H., C.A.B., J.A.P., P. Bowness, P.J.S., and N.J.R., manuscript in preparation). Zinc fingers were thought to be confined to eukaryotes, but recent studies have indicated the presence of Krüppel-like zinc fingers in some prokaryotes (5,(44)(45)(46), although they remain to be confirmed by structure determination.…”
Section: Methodsmentioning
confidence: 99%
“…Mutants lacking the smtA locus are hypersensitive to elevated zinc (5-fold), but otherwise viable (4). In addition to sequestering excess, it has been postulated that SmtA may be involved in controlling the intracellular distribution of zinc (5), but a specific partner (protein or DNA) for interaction with SmtA has not yet been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genotype of transformants was checked by PCR using primers 3 and 5Ј-GATTAACCGTTGACCAGCGCTAG-3Ј, which anneal to cbiE sequences flanking the site of cat insertion. The detected products revealed transformants to be merodiploid, with some chromosomes retaining cbiE and others containing cat within cbiE, with analogy to previous attempts to disrupt an essential cyanobacterial gene (24).…”
mentioning
confidence: 96%